Trends and Developments of Educational Media in Inclusive Education for Children With Disabilities: A Bibliometric Analysis (Scopus 2015–2024) - Zulfikasari, Sony; Edy Mulyono, Sungkowo; Arbarini, Mintarsih (Exceptionality Education International)

(untitled) (University of Western Ontario, 2026)
The study mapped research trends and the development of educational media in special and inclusive education through a bibliometric analysis of publications indexed in the Scopus database. Data were collected in April 2025, covering journal articles published from 2015 to 2024 to ensure full‑year comparability. The search strategy employed a query combining keywords related to special needs education, inclusive education, teaching models, and educational media. A total of 322 articles were analyzed using descriptive statistics, VOSviewer for keyword-co-occurrence mapping, and Biblioshiny for thematic-trend analysis. The results indicated a steady increase in research attention to special needs and inclusive education during the past decade, particularly to assistive technology and instructional media. This trend was observed within the dataset of inclusive and special education publications, including the models and instructional media developed. The dominant themes included inclusive education, special needs instruction, assistive technology, and media development, suggesting the need for further studies integrating pedagogical design with technological innovation. Thematic-evolution analysis showed a progressive shift. The early phase (2015–2020) emphasized accessibility and assistive technologies, the middle phase (2021–2022) focused on teacher readiness and Universal Design for Learning, and the recent phase (2023–2024) was marked by the integration of immersive technologies such as virtual reality and augmented reality. Overall, the findings highlight a transition from access‑oriented innovations to systemic digital transformation, positioning technology as a strategic tool to strengthen teacher competence, institutional policy, and cultural responsiveness.